2022
DOI: 10.1038/s41467-022-34668-w
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis and thrombocytopenia after vaccination against and infection with SARS-CoV-2 in the United Kingdom

Abstract: Population-based studies can provide important evidence on the safety of COVID-19 vaccines. Using data from the United Kingdom, here we compare observed rates of thrombosis and thrombocytopenia following vaccination against SARS-CoV-2 and infection with SARS-CoV-2 with background (expected) rates in the general population. First and second dose cohorts for ChAdOx1 or BNT162b2 between 8 December 2020 and 2 May 2021 in the United Kingdom were identified. A further cohort consisted of people with no prior COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…However, limited post-vaccination increments in D-dimer and F 1 +2 , along with endothelial stunning may become significant, albeit weakly, at a population level. A pivotal paper published online in November 2022 [33] reported minor, but statistically significant, 12 % and 25 % higher risks of venous thromboembolism and pulmonary embolism, respectively, following the first dose of either Comirnaty or Vaxzevria compared to the general population. Corresponding risks observed following SARS-Cov-2 infection from September 1st 2020 up to May 2nd 2021 were respectively 61-fold and 49-fold higher; nonetheless, our findings may at least partially explain the rare occurrence of venous thromboembolic complications in subjects with hyper-inflammatory reactions to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited post-vaccination increments in D-dimer and F 1 +2 , along with endothelial stunning may become significant, albeit weakly, at a population level. A pivotal paper published online in November 2022 [33] reported minor, but statistically significant, 12 % and 25 % higher risks of venous thromboembolism and pulmonary embolism, respectively, following the first dose of either Comirnaty or Vaxzevria compared to the general population. Corresponding risks observed following SARS-Cov-2 infection from September 1st 2020 up to May 2nd 2021 were respectively 61-fold and 49-fold higher; nonetheless, our findings may at least partially explain the rare occurrence of venous thromboembolic complications in subjects with hyper-inflammatory reactions to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…As per the previous evidence, most adverse events following vaccination were nonserious, such as fatigue, headache, and myalgia 3 . Although rare, vaccine‐induced thrombotic complications have recently attracted extensive concern 4,5 …”
Section: Introductionmentioning
confidence: 75%
“…3 Although rare, vaccine-induced thrombotic complications have recently attracted extensive concern. 4,5 Thrombotic microangiopathy (TMA), a pathological manifestation observed in multiple diseases, is characterized by thrombocytopenia, microangiopathic hemolytic anemia, and ischemic organ damage. 6,7 Thrombotic thrombocytopenic purpura (TTP) and atypical hemolytic uremic syndrome (aHUS) are significant subtypes of TMA.…”
Section: Introductionmentioning
confidence: 99%
“…21 This issue has been compounded by the COVID-19 pandemic as there is evidence of increased VTE events after COVID infection. 22 This may be of particular relevance to potential donors with recent symptomatic or asymptomatic COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…— 20 Studies have shown that LDH may be associated with a pro‐coagulant profile in the early post‐operative period which could potentially increase VTE risk 21 . This issue has been compounded by the COVID‐19 pandemic as there is evidence of increased VTE events after COVID infection 22 . This may be of particular relevance to potential donors with recent symptomatic or asymptomatic COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 99%